2012
DOI: 10.1021/mp300240m
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tumor Homing and Tissue Penetration of the Filamentous Plant Viral Nanoparticle Potato virus X

Abstract: Nanomaterials with elongated architectures have been shown to possess differential tumor homing properties compared to their spherical counterparts. Here, we investigate whether this phenomenon is mirrored by plant viral nanoparticles that are filamentous (Potato virus X) or spherical (Cowpea mosaic virus). Our studies demonstrate that Potato virus X (PVX) and Cowpea mosaic virus (CPMV) show distinct biodistribution profiles and differ in their tumor homing and penetration efficiency. Analogous to what is seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
180
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 143 publications
(190 citation statements)
references
References 51 publications
10
180
0
Order By: Relevance
“…We conjugated PVX with the near-infrared fluorophore A647 to allow the imaging and tracking of the formulations, and also with PEG to enhance particle solubility and stability. A647 and PEG5000 were chosen because we recently showed that A647-PVX-PEG is suitable for tumor homing and imaging in preclinical tumor animal models [9]. We therefore designed the PVX formulation according to our published procedures (Figure 1A) [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We conjugated PVX with the near-infrared fluorophore A647 to allow the imaging and tracking of the formulations, and also with PEG to enhance particle solubility and stability. A647 and PEG5000 were chosen because we recently showed that A647-PVX-PEG is suitable for tumor homing and imaging in preclinical tumor animal models [9]. We therefore designed the PVX formulation according to our published procedures (Figure 1A) [9].…”
Section: Resultsmentioning
confidence: 99%
“…Leaves were harvested 10–14 days after mechanical inoculation with 5 μg of purified PVX particles. PVX was purified as described earlier (please see Supplementary Material online at www.futuremedicine.com/doi/suppl/13.75) [9]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We established bioconjugation protocols targeting surface-exposed lysines using N-hydroxysuccinimide or Cu(I)-catalyzed azide-alkyne cycloaddition (click chemistry) enabling efficient functionalization of PVX with biotin linkers, fluorophores, PEG, targeting ligands, etc. [12][13][14][15] To date PVX has been used for epitope presentation approaches in vaccine development; [9,16] chimeric PVX particles have also been combined with enzymes for the fabrication of novel biocatalysts, [17] and PVX is undergoing development as a novel carrier for oncological imaging and therapeutic intervention. [12][13][14][15] To extend the application of PVX, we set out to combine the platform technology with protein A fragments for functionalization for antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] To date PVX has been used for epitope presentation approaches in vaccine development; [9,16] chimeric PVX particles have also been combined with enzymes for the fabrication of novel biocatalysts, [17] and PVX is undergoing development as a novel carrier for oncological imaging and therapeutic intervention. [12][13][14][15] To extend the application of PVX, we set out to combine the platform technology with protein A fragments for functionalization for antibodies. The potential application of such antibody-functionalized filaments is envisioned in medical imaging or drug delivery when combined with contrast agents and or toxic payloads as well as in diagnostics; the latter was investigated in the present study.…”
Section: Introductionmentioning
confidence: 99%